Measuring the Nonmonetary Component of General Value of Jobs - Aityan, Sergey K.; Ivanov-Schitz, Alexey K.; Thapa, Shankar (Advances in Social Sciences Research Journal, 2016)
The concept of value has been a central concern of economics since its inception as a discipline. The labor theory of value in classical economics was followed by the neoclassical perceptional theory of utility, and behavioral economics introduced a psychological track in it. The recently introduced theory of general value makes the next step by introducing two distinct components of value: monetary and nonmonetary. The introduction of the nonmonetary component of value helps explain many types of decisions and choices, which were not clearly understood before, and helps with the strategic planning and actions. This paper introduces a methodology of measuring nonmonetary value of jobs in the perception of people. The indifference point between two choices is used to measure the difference if nonmonetary components in terms of the difference of the monetary components with the opposite sign. This method was used to measure relative nonmonetary values (the difference of the monetary components) of various jobs in the perception of different social groups.